A Review of Pathogen Transmission at the Backyard Chicken–Wild Bird Interface - Ayala, Andrea J.; Yabsley, Michael J.; Hernandez, Sonia M. (Frontiers in Veterinary Science, 2020)
Habitat conversion and the expansion of domesticated, invasive species into native habitats are increasingly recognized as drivers of pathogen emergence at the agricultural-wildlife interface. Poultry agriculture is one of the largest subsets of this interface, and pathogen spillover events between free-ranging poultry and wild birds are becoming more commonly reported. Native wild bird species are under numerous anthropogenic pressures, but the risks of pathogen spillover from domestic chickens have been historically underappreciated as a threat to wild birds. Now that the backyard chicken industry is one of the fastest growing industries in the world, it is imperative that the principles of biosecurity, specifically bioexclusion and biocontainment, are legislated and implemented.We reviewed the literature on spillover events of pathogens historically associated with poultry into wild birds. We also reviewed the reasons for biosecurity failures in backyard flocks that lead to those spillover events and provide recommendations for current and future backyard flock owners.